Pemetaan Penggunaan Lahan Pertanian di Kota Kupang menggunakan Penginderaan Jauh - Rambu Ngana, Frederika (Agriculture Faculty of Flores University, 2024)
Every year, the districts and city of Agriculture Services in the Nusa Tenggara Timur (NTT) province report the area of agricultural land use to the NTT Provincial Agriculture and Food Security Service. The agricultural land area was measured manually by the field officers of the City and Districts of Agriculture Services. This research aims to map and measure the area of agricultural land use using remote sensing. Kupang City was used as a case study location. The remote sensing data used in this research was Landsat-9 satellite imageries from the U.S. Geological Survey in August 2022. These images were then classified based on classes paddy rice fields, non paddy rice fields, and nonagricultural fields. The classification was carried out using the Random Forest algorithm on QGIS software. This classification was based on the training sites of each land use type in Kupang City taken with GPS. The result of the research is a map of agricultural land use in Kupang City. This research shows that remote sensing allows the NTT provincial Agriculture and Food Security Service to determine the location and calculate the area of the agricultural land use in the NTT Province region quickly and accurately without a field survey. To map the agricultural land use in NTT more effectively using remote sensing, the Landsat image should be selected on the planting time. In addition, it is very important to ensure that the area on the administrative map used to crop the Landsat image corresponds to the actual area.